DETERMINASI DETERMINASI FAKTOR TATA KELOLA DAN KOMPETENSI KEBERLANJUTAN TERHADAP KUALITAS SUSTAINABILITY REPORT: : Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2017–2023 - Rachmah, Dewi Nailur; Yulianto, Agung (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the influence of sustainability committees, background diversity (educational level), sustainability training, executive remuneration, environmental performance, and external assurance on the quality of sustainability reports in energy sector companies listed on the Indonesia Stock Exchange from 2017 to 2023. A quantitative approach was applied using panel data regression with a Fixed Effect Model. The sample consisted of 75 analysis units selected through purposive sampling. The results show that the sustainability committee, sustainability training, and external assurance have a significant positive effect on the quality of the sustainability report. In contrast, background diversity, executive remuneration, and environmental performance do not show a significant effect. The adjusted R² value of 0.418942 indicates that the model explains 41.89% of the variation in report quality. These findings underscore the significance of institutional and professional support as key factors influencing the quality of sustainability reports. Future studies are recommended to incorporate additional variables, such as regulatory pressure and corporate culture, and to consider qualitative approaches or third-party assessments.